Pedagogy of tenderness to reduce aggressive behavior in children - Cajusol Santisteban, Carmen (2021)
Abstract This article describes the results of the implementation of a pedagogy program that is based on tenderness, which was applied in two groups of children of the initial level in order to discover the positive impact on the reduction of aggressive manifestations that children presented. Therefore, the objective focused on determining the impact of the pedagogy program based on tenderness to counteract aggressive behaviors in boys and girls from IEI N ° 313 Héctor Aurich from the district of Ferreñafe and IEI San Gabriel N ° 051 from the district of Pomalca. According to the research methodology, it was an application with a quasi-experimental design, where a pre and post test was used as information collection tools in the study sample, evaluating the dependent variable of aggressiveness. However, the entire population was taken as a sample because it was small and had access to them, being 180 girls and boys from the two aforementioned institutions. The program is based mainly on workshops where the principles involved to eradicate the problem are the parents of the children, achieving successful results, reducing the number of physical aggression found from 57% to 23%. Likewise, verbal aggressive behaviors reduced from 76% to 30% and finally, from 66% to 26%, aggressive psychological behavior. Finally, pedagogy programs are important tools that generate successful results, if parents and teachers apply them continuously, showing sensitivity, interest and responsibility to guide with love and values, allowing them to grow up healthy and happy. Keywords: pedagogy of tenderness, aggressive behaviors, pedagogy program